UJI PREDIKSI UMUR KEANDALAN OPERASI RADIAL BALL BEARING PADA MOTOR DIESEL SINGLE CYLINDER DENGAN PENDEKATAN AMBANG BATAS KEAUSAN - Hatuwe, Mohammad Rusdy; Djaja, Yuhani (Bina Teknika, 2016)
Factually where the bearingss are not functioning properly makes the performance of the entire system will decrease or can not work properly. In this study, the wear test data that will be used is the data for the operating hours of 100 hours, 200 hours, 300 hours, 400 hours and 500 hours and the first converted into a linear function to obtain a threshold of wear of each specimen. In accordance with the objectives to be achieved in this study was to determine the relationship between the limits hours of operation and wear limit set maximum ball bearings manufacturer. The data used in this study is through the mechanism of experimental tests on Diesel engines Yanmar 15 HP, 1700 RPM using 3 specimens to be validated. Furthermore, these data will be generated from a particular distribution which will provide an overview wear limit as a function of operating hours.